"It's not the Investment, it's the Services": Making Visible the True Impact of Infrastructure in Latin America (Desarrollo Económico. Revista de Ciencias Sociales, 2023)
Infrastructure is key for growth, competitiveness and well-being. Its importance has been traditionally measured by infrastructure investment. However, the services that infrastructure capital provides to households and firms are not integrated into the analysis. These activities include services contracted ("for hire") and self-provided ("in house"), which are not classified as such in the GDP. Activities “In house” are auto production of energy, transport of companies with their own cargo fleet and new phenomena such as Uberization and "commuting" and tourism of households carried out by their own vehicles. This paper proposes a methodology to estimate the functional GDP of infrastructure services, pioneering in Latin America. The estimates were made for the three main countries of Latin America their geographical size, GDP and population: Argentina, Brazil and Mexico. Functional GDP of infrastructure services represents an average 14% of GDP for the three countries. This outstanding figure multiplies by eight the traditional infrastructure investment, almost 2% of GDP. Transport by own account is almost 50% of the traditional GDP of this activity.
Keywords: Public Services, Road Infrastructure, Infrastructure and Transportation, National Accounts, Economic Development